Rabies Elimination in Rural Kenya: Need for Improved Availability of Human Vaccines, Awareness and Knowledge on Rabies and Its Management Among Healthcare Workers - Chuchu, Veronicah Mbaire; Kitala, Philip Mwanzia; Bichanga, Philet; Ksee, Daniel; Muturi, Mathew; Mwatondo, Athman; Nasimiyu, Carolyne; Maritim, Marybeth; Mutono, Nyamai; Beyene, Tariku J.; Druelles, Sophie; Hampson, Katie; et al. (Frontiers in Public Health, 2022)
Background: In Africa, rabies causes an estimated 24,000 human deaths annually. Mass dog vaccinations coupled with timely post-exposure prophylaxis (PEP) for dog-bite patients are the main interventions to eliminate human rabies deaths. A well-informed healthcare workforce and the availability of rabies biologicals at health facilities are critical in reducing rabies deaths. Here, we assess awareness and knowledge regarding rabies and the management of rabies among healthcare workers, and PEP availability in rural eastern Kenya. Methodology: We interviewed 73 healthcare workers from 42 healthcare units in 13 wards in Makueni and Kibwezi West sub-counties, Makueni County, Kenya. We collected data on their demographics, years of work experience, knowledge and awareness of rabies, management of bite and rabies patients, and availability of rabies biologicals at the study health facilities. Results: Awareness about rabies and management of bite patients was low among the healthcare workers. Less than a quarter of the healthcare workers were aware of the World Health Organization categorization of bite wounds that guides the use of PEP. Eighteen percent (n=13) of healthcare workers reported they would administer PEP for category I exposures, suggesting potential non-judicial use of PEP. PEP was primarily administered intramuscularly, with only 11% (n=8) aware of the dose-sparing, cost-saving intradermal route. Only one of six respondents who had seen patients with acute encephalitis considered rabies as a differential diagnosis highlighting the low index of suspicion for rabies. None of the health facilities stocked rabies immunoglobulins, and only 5 of 42 had rabies vaccines in-stock at the time of the survey. Conclusion: Significant gaps remain in healthcare worker's knowledge regarding recommended care of bite patients and rabies diagnosis. Educational and awareness programs on rabies and its management for healthcare workers and improvements in access to life-saving PEP are urgently needed to support rabies elimination efforts.